EDUCATIONAL TRANSFORMATION THROUGH RESOURCE MANAGEMENT STRATEGIES: PERSPECTIVES AT TELKOM VOCATIONAL SCHOOL IN BANJARBARU - Rama Meiagriza; Jabal Jamalullail; Rama Aditya Pratama; Aslamiah; Ahmad Suriansyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe resource management strategies (human, financial, infrastructure, and technology) in supporting educational transformation at SMK Telkom Banjarbaru as a technology-based vocational school. A descriptive qualitative approach was applied with data collection through semi-structured interviews, participatory observation, and document studies of the principal, teachers, facility managers, and industry partners. Data analysis followed Miles and Huberman's interactive model with triangulation of sources and methods to ensure validity. The results show that SMK Telkom Banjarbaru implements annual industry needs analysis, intensive training for technical and non-technical human resources, laboratory facility upgrades, and industry partnerships for internship programs. Supporting factors include a commitment to contextual analysis and cross-sector collaboration, while the main obstacles include delays in implementation, unscheduled facility maintenance, limited industry partners, and infrequent soft skills training. The novelty of this research lies in its contextual focus on technology vocational schools with integrated industry partnerships, alignment of workplace competencies, and productive facility management. Practical recommendations include strengthening budget maintenance mechanisms, KPI monitoring systems, expanding partnerships, and regular soft skills training programs. Thus, resource management can be a catalyst for sustainable educational transformation, producing competent and work-ready graduates